Age, Gender, and Muscle Strength: a Study Based on Indonesian Samples - Henny, Henny; Iridiastadi, Hardianto; Sutalaksana, Iftikar Zahedi (Makara Journal of Technology, 2012)
Age and gender have been commonly used as a main criterion in accepting a job aplicant, but it is usually not clear how these affect job performance. While a number of recent studies have been done that describe the relationships between age, gender, and participants capacity (e.g., muscle strength), the results have been inconclusive. In Indonesia, in particular, such issues have been rarely investigated, and it is still important to study the issue since the relationships between these factors are population-specific. This study aimed at describing the relationships between age and muscle strength among workers for both genders. Ninety-six male and female workers (aged 18–65) were recruited in this study, and data on handgrip and lower back strength were collected. Findings of this study show that peak hand-grip strength occured at the age of around 35-40 years of age, regardless of gender. Maximum lower back strengh was identified at the age of 31-35 years old (for males) and 26-30 years old (for females). Comparisons between two extreme age groups (18-20 vs. 61-65 years of age) showed a mean strength decline of 50% for hand-grip and 30% for the lower back. For both protocols, female participants tended to have lower muscle strength (70-80% of their male counterparts). Findings of this study can be used as a basis in evaluating physical requirements of a job, and the corresponding factors (age and gender) relevant for the job.